Vascular plants on the islands and peninsulas of Maloe More (Lake Baikal): patterns of diversity and species turnover - Chepinoga VV; Zverev VE; Zvereva EL; Kozlov MV (FINNISH ENVIRONMENT INST, 2022)
Unique biota of the Lake Baikal region face many threats due to increasing human activities. We documented spatial patterns in diversity of vascular plants, explored effects of natural (bird colonies) and human-induced (tourism) disturbances on species richness of semi-desert and steppe-desert plant communities of 12 islands and 4 peninsulas, and estimated species turnover within a 30-year period. Floras of surveyed islands/peninsulas contained 9 to 143 species; species area relationship followed the power law model. Species richness did not change between 1979 and 2009, but the proportion of ruderal species doubled during this period. Mean relative turnover rate was 1.17% of species per year. The islands with large bird colonies had lower species richness than the islands with small or no colonies. Imposing restrictions on tourist visitation to at least three islands (Zamogoj, Khubyn and Khunuk) is a feasible way to conserve substantial part of regional biodiversity.